Effect of Stacked Sodium Bicarbonate Loading on Repeated All-out Exercise - Dalle, Sebastiaan; De Smet, Stefan; Geuns, Willem; Rompaye, Bart Van; Hespel, Peter; Koppo, Katrien (International Journal of Sports Medicine, 2019)
The purpose of this study was to evaluate whether NaHCO3, administered via a 9-h stacked loading protocol (i.e. repeated supplementation with small doses in order to obtain a gradual increase in blood [HCO3-]), has an ergogenic effect on repeated all-out exercise. Twelve physically active males were randomly assigned to receive either NaHCO3 (BIC) or placebo (PL) in a double-blind cross-over design. NaHCO3 supplementation was divided in three identical 3-h cycles: a 6.3 g bolus at the start, followed by 2.1 g doses at +1-h and +2-h, yielding a total NaHCO3 intake of 0.4 g·kg−1 BM over 9-h. At the end of each cycle, participants performed 2-min all-out cycling. Capillary blood samples were analyzed for [HCO3-], pH and [La-]. Pre-exercise blood [HCO3-] in PL decreased from 25.6±0.2 mmol·L−1 in bout 1 to 23.6±0.2 mmol·L−1 in bout 4, while increasing from 25.5±0.2 to 31.2±0.4 mmol·L−1 in BIC (P<0.05). Concomitantly, pre-exercise pH values gradually decreased in PL (from 7.41±0.00 to 7.39±0.01) and increased in BIC (from 7.41±0.01 to 7.47±0.01; P<0.05). Mean power output of the four bouts was higher in BIC (428±20 W) than in PL (420±20 W; P<0.05). The ergogenic effect on repeated all-out exercise occurred in the absence of gastrointestinal distress.
Keywords: buffer capacity; muscle energetics; sprint performance; cycling